Hamoraon, Hagabeon & Hasangapon as The Basic Philosophy in Educating Children - Dalimunthe, Irwan Saleh; Lubis, Agus Salim (el Harakah: Jurnal Budaya Islam, 2019)
Cultural and religious values of life for the people in South Tapanuli form the perspective of philosophy and various local wisdom. One of the principles they hold strongly is known as 3H they are; hamoraon (character and wealth), hagabeon (successful offspring) and hasangapon (influential and respectable). This research focused on how the 3H principles strongly encourage parents to provide knowledge for the future preparation of their children. Muslim communities are fanatics in religion, meanwhile the most dominant value in giving encouragement to school is not religious teachings, since religion is only a supporting factor of learning (Q.S. 58:11), and the cultural view of 3H is as the basis of the education. It was carried out by in-depth interview techniques with a sociological approach to respondents who were intentionally searched and determined, and the parents or families who were relatively successful in school and in changing lives, and also respectable in the community. It is found that the community is firmed with the 3H value, in which parents were tireless, even sacrificing everything so that their children succeed in enjoying welfare, prosperity and living respect. Nilai-nilai budaya dan agama bagi masyarakat di Tapanuli Selatan membentuk perspektif filsafat dan berbagai kearifan lokal. Salah satu prinsip yang mereka pegang dengan kuat yaitu yang dikenal sebagai 3H; hamoraon (karakter dan kekayaan), hagabeon (keturunan sukses) dan hasangapon (berpengaruh dan terhormat). Penelitian ini berfokus pada seberapa kuat prinsip 3H mendorong orang tua untuk memberikan pengetahuan bagi persiapan masa depan anak-anak mereka. Komunitas Muslim fanatik dalam agama, sedangkan nilai yang paling dominan dalam memberikan dorongan kepada sekolah bukanlah ajaran agama, karena agama hanya merupakan faktor pendukung pembelajaran (Q.S. 58:11), dan pandangan budaya 3H adalah sebagai dasar pendidikan. Penelitian ini menggunakan teknik wawancara mendalam dengan pendekatan sosiologis kepada responden yang dipilih dan ditentukan, serta melibatkan orang tua atau keluarga yang relatif sukses dalam pendidikan dan dalam mengubah kehidupan, juga dihormati di masyarakat. Ditemukan bahwa masyarakat teguh dengan nilai 3H, di mana orang tua tidak kenal lelah, bahkan mengorbankan segalanya sehingga anak-anak berhasil berhasil menikmati kesejahteraan, kemakmuran dan penghormatan hidup.